Biomarkers of Nutrition for Development (BOND)-Vitamin A Review - Tanumihardjo, Sherry A; Russell, Robert M; Stephensen, Charles B; Gannon, Bryan M; Craft, Neal E; Haskell, Marjorie J; Lietz, Georg; Schulze, Kerry; Raiten, Daniel J (The Journal of nutrition, 2016)
The Biomarkers of Nutrition for Development (BOND) project is designed to provide evidence-informed advice to anyone with an interest in the role of nutrition in health. The BOND program provides information with regard to selection, use, and interpretation of biomarkers of nutrient exposure, status, function, and effect, which will be especially useful for readers who want to assess nutrient status. To accomplish this objective, expert panels are recruited to evaluate the literature and to draft comprehensive reports on the current state of the art with regard to specific nutrient biology and available biomarkers for assessing nutritional status at the individual and population levels. Phase I of the BOND project includes the evaluation of biomarkers for 6 nutrients: iodine, folate, zinc, iron, vitamin A, and vitamin B-12. This review of vitamin A is the current article in this series. Although the vitamin was discovered >100 y ago, vitamin A status assessment is not trivial. Serum retinol concentrations are under homeostatic control due in part to vitamin A's use in the body for growth and cellular differentiation and because of its toxic properties at high concentrations. Furthermore, serum retinol concentrations are depressed during infection and inflammation because retinol-binding protein (RBP) is a negative acute-phase reactant, which makes status assessment challenging. Thus, this review describes the clinical and functional indicators related to eye health and biochemical biomarkers of vitamin A status (i.e., serum retinol, RBP, breast-milk retinol, dose-response tests, isotope dilution methodology, and serum retinyl esters). These biomarkers are then related to liver vitamin A concentrations, which are usually considered the gold standard for vitamin A status. With regard to biomarkers, future research questions and gaps in our current understanding as well as limitations of the methods are described.